2006
DOI: 10.1002/we.206
|View full text |Cite
|
Sign up to set email alerts
|

Technical aspects of status and expected future trends for wind power in Denmark

Abstract: The power system of Denmark is characterized by significant incorporation of wind power. Presently, more than 20% of the annual electricity consumption is covered by electricity‐producing wind turbines. The largest increase in grid‐incorporated wind power is expected to come from large (offshore) wind farms operating as large wind power plants with ride‐through solutions, connected to the high‐voltage transmission system and providing ancillary services to the system. In Denmark there are presently two offshor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 2 publications
0
27
0
Order By: Relevance
“…Large offshore wind farms may inject significant power fluctuations into power systems [9], and such power fluctuations may affect neighbouring power systems, if it is not appropriately dealt with. For example, the offshore wind farm Horns Rev A in Western Denmark produces more intense active power fluctuations than the aggregated wind power produced by land based wind farms in the western Danish power system and shows frequent active power fluctuations within periods of tens of minutes, the power gradients reach 15 MW per minute, thus the 160 MW wind farm have the output power change between zero and the rated power in 10-15 min [10]. The system power balance could also be worsen by the deviations from the planned power exchanges between Norway and Sweden.…”
Section: Wind Power Fluctuation and Interconnected Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Large offshore wind farms may inject significant power fluctuations into power systems [9], and such power fluctuations may affect neighbouring power systems, if it is not appropriately dealt with. For example, the offshore wind farm Horns Rev A in Western Denmark produces more intense active power fluctuations than the aggregated wind power produced by land based wind farms in the western Danish power system and shows frequent active power fluctuations within periods of tens of minutes, the power gradients reach 15 MW per minute, thus the 160 MW wind farm have the output power change between zero and the rated power in 10-15 min [10]. The system power balance could also be worsen by the deviations from the planned power exchanges between Norway and Sweden.…”
Section: Wind Power Fluctuation and Interconnected Networkmentioning
confidence: 99%
“…An area grid controller can perform the secondary control with the central power plants and tie lines to other neighbouring power systems, including the HVDC connections [10]. The area grid controller can cooperate with wind power dispatch centre for overall system power dispatch and control to deal with the wind power fluctuations.…”
Section: Wind Farm Dispatch and Virtual Power Plantmentioning
confidence: 99%
“…As a first step towards this understanding, Akhmatov et al [7] reported that at a temporal resolution of 10 min, certain weather conditions at Horns Rev and in particular north-westerly winds very much favored large wind power fluctuations. Then, Sørensen et al [8] proposed an aggregated model of individual wind turbines and showed its relative ability to simulate consistent wind power fluctuations at different time scales, from a few minutes up to 2 h ahead.…”
Section: Motivations Based On the State-of-the-artmentioning
confidence: 99%
“…Authors such as Parsons et al [23] focus on the demands exerted by wind turbines on external ancillary service providers and Gjengedal [24] argues that it may not be optimal to equip wind turbines with the techniques required to supply ancillary services. However, as Akhmatov et al [25] notes, progressively stricter grid codes tend to have improved wind turbines and therefore, they should be able to supply ancillary services in the future through the use of power converter coupling to the grid. Ride-though capability has been one of the focus areas of the increasingly stricter grid codes adding to short-circuit power.…”
Section: Article In Pressmentioning
confidence: 99%